2022
DOI: 10.1029/2021sw002993
|View full text |Cite
|
Sign up to set email alerts
|

CMEs and SEPs During November–December 2020: A Challenge for Real‐Time Space Weather Forecasting

Abstract: Predictions of coronal mass ejections (CMEs) and solar energetic particles (SEPs) are a central issue in space weather forecasting. In recent years, interest in space weather predictions has expanded to include impacts at other planets beyond Earth as well as spacecraft scattered throughout the heliosphere. In this sense, the scope of space weather science now encompasses the whole heliospheric system, and multipoint measurements of solar transients can provide useful insights and validations for prediction mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 202 publications
0
13
0
Order By: Relevance
“…Although such a transport process might have contributed to shaping the SEP event detected at Bepi and Earth, our modeling suggests that variations of the energetic particle emission at the CME-driven shock due to the shock interacting with the varying background solar wind, and in particular the SIR, may have played a dominant role. A similar explanation for another event was proposed by Ding et al (2022), where the authors used the improved Particle Acceleration and Transport in the Heliosphere model (iPATH; see Hu et al 2017, and references therein) to study the SEP event on 2020 November 29, observed by Solar Orbiter, Parker Solar Probe, STEREO-A, and spacecraft near Earth and Mars (Kollhoff et al 2021;Palmerio et al 2022). The CME generating that event also interacted with a high-speed stream, and the authors likewise concluded that this interaction and the resulting deformation of the shock wave played an important role in the variation of time-intensity profiles measured at different spacecraft.…”
Section: Summary and Discussionmentioning
confidence: 71%
“…Although such a transport process might have contributed to shaping the SEP event detected at Bepi and Earth, our modeling suggests that variations of the energetic particle emission at the CME-driven shock due to the shock interacting with the varying background solar wind, and in particular the SIR, may have played a dominant role. A similar explanation for another event was proposed by Ding et al (2022), where the authors used the improved Particle Acceleration and Transport in the Heliosphere model (iPATH; see Hu et al 2017, and references therein) to study the SEP event on 2020 November 29, observed by Solar Orbiter, Parker Solar Probe, STEREO-A, and spacecraft near Earth and Mars (Kollhoff et al 2021;Palmerio et al 2022). The CME generating that event also interacted with a high-speed stream, and the authors likewise concluded that this interaction and the resulting deformation of the shock wave played an important role in the variation of time-intensity profiles measured at different spacecraft.…”
Section: Summary and Discussionmentioning
confidence: 71%
“…Although there is data gap from MAVEN, comparing with the plasma data observed by Mars Express (see in Figure A3 from Palmerio et al. (2022)), the predicted CME peak time at Mars is around 22 hr later than the observed peak time. Palmerio et al.…”
Section: Comparing the Model's Performancementioning
confidence: 76%
“…By projecting the GCS wireframe onto the plane of sky of the coronagraph imagery, a user can adjust the six free parameters until the obtained shell visually matches the CME's appearance. Forward modeling with the GCS technique is often performed to derive CME input parameters for analytical (e.g., Kay & Gopalswamy 2017;Čalogović et al 2021) and MHD (e.g., Scolini et al 2020;Palmerio et al 2022a) simulations, but in the case of the 2015 July 9 event, there are two factors that make the analysis more complex than usual. First, the Solar Terrestrial Relations Observatory Ahead (STEREO-A) spacecraft was in superior conjunction with Earth, meaning that most of its instruments were not operational and only the SOHO (Earth) vantage point is available.…”
Section: Cme Evolution In the Coronamentioning
confidence: 99%
“…This is likely due to the specific geometry and magnetic description of each of the CME ejecta, which may in turn yield different interaction outcomes. For example, in the EUHFORIA +Spheroid run (Figure 4(b)), the lack of a magnetized ejecta is not expected to result in a realistic interaction process (see also Palmerio et al 2022a), but rather in a CME-like disturbance propagating more or less straightforwardly through a background wind. In the EUHFORIA+Spheromak run (Figure 4(c)), the lack of CME legs may represent less of an "obstacle" to the ambient solar wind, which in turn may be able to flow about the ejecta with minimal interaction of the two flux systems.…”
Section: Large-scale Structure Of the Cmementioning
confidence: 99%